การศึกษาตัวบ่งชี้การประเมินคุณภาพการศึกษาภายในระดับกองและภาควิชากองการศึกษา วิทยาลัยพยาบาลกองทัพบก The study of indicator for internal education quality Assessment for the division and departments of education division, The Royal Thai Army Nursing College - พูนชัย, ศิริพร; อินทรรัตน์, อภิญญา; อังคะนาวิน, อุษณีย์; เบาะเปลี่ยน, สุวีณา (Journal of The Royal Thai Army Nurses, 2015)
การวิจัยนี้มีวัตถุประสงค์เพื่อศึกษา คัดสรร และสร้างตัวบ่งชี้การประเมินคุณภาพการศึกษาภายในระดับกอง และภาควิชา ของกองการศึกษาวิทยาลัยพยาบาลกองทัพบก วิธีการดำเนินการวิจัยในครั้งนี้เป็นการวิจัยเชิงปฏิบัติการแบบมีส่วนร่วมแบ่งเป็น 2 ระยะ คือ ระยะที่ 1 การศึกษา คัดสรร และสร้างตัวบ่งชี้ และระยะที่ 2 การตรวจสอบคุณภาพและทดลองใช้ตัวบ่งชี้ผู้เข้าร่วมในการวิจัยครั้งนี้ ได้แก่ ผู้บริหารและอาจารย์ กองการศึกษาวิทยาลัยพยาบาลกองทัพบก จำนวนทั้งสิ้น 40 คน วิธีการเก็บรวบรวมข้อมูลใช้การศึกษาเอกสาร การสนทนากลุ่มผู้บริหารและการสำรวจความคิดเห็นของผู้มีส่วนเกี่ยวข้อง เครื่องมือที่ใช้ในงานวิจัยนี้มี 2 ชุด ได้แก่ 1) แบบสัมภาษณ์แบบกึ่งโครงสร้างสำหรับการสนทนากลุ่ม และ 2) แบบสำรวจความคิดเห็นต่อ (ร่าง) ตัวบ่งชี้ การวิเคราะห์ข้อมูลโดยการวิเคราะห์เนื้อหา และการวิเคราะห์หาค่าดัชนีความคิดเห็นสอดคล้องตรงกันผลการศึกษาพบว่ากองการศึกษาควรดำเนินการประกันคุณภาพการศึกษาภายในให้ครบถ้วนทั้ง 9 องค์ประกอบ ทั้งในระดับกอง และระดับภาควิชา โดยควรคัดสรรมาจากตัวบ่งชี้ในระดับวิทยาลัยและเห็นด้วยกับการนำเกณฑ์รับรองสถาบันของสภาการพยาบาลและตัวบ่งชี้ของการประกันคุณภาพหลักสูตรและกาจัดการเรียนการสอนของมาตรฐานคุณวุฒิระดับปริญญาตรีสาขาพยาบาลศาสตร์ มาใช้ในการสร้างเป็นตัวบ่งชี้เพิ่มเติมให้สอดคล้องกับการดำเนินงานของกองการศึกษา ตัวบ่งชี้ในระดับกองมี 34 ตัวบ่งชี้ และระดับภาควิชามี 25 ตัวบ่งชี้ ประกอบด้วยตัวบ่งชี้ประเภทกระบวนการมากที่สุด ในระดับกองคิดเป็นร้อยละ 58.92 และในระดับภาควิชา คิดเป็นร้อยละ 62.50 ส่วนที่มาของตัวบ่งชี้มาจากตัวบ่งชี้ระดับวิทยาลัยมากที่สุดในระดับกอง คิดเป็นร้อยละ 70.58 และในระดับภาควิชาคิดเป็นร้อยละ 75.00 ผลการตรวจสอบคุณภาพของร่างตัวบ่งชี้การประเมินโดยผู้เชี่ยวชาญ มีค่า IOC มากกว่า 0.70 ในทุกองค์ประกอบ ผลการสำรวจความคิดเห็นพบว่า ตัวบ่งชี้ส่วนใหญ่มีค่าดัชนีความคิดเห็นสอดคล้องตรงกันในระดับปานกลางขึ้นไป ผลการทดลองใช้ พบว่า ทั้งในระดับกองและภาควิชาสามารถเขียนรายงานและประเมินตนเองได้ในทุกตัวบ่งชี้ ส่วนการเปรียบเทียบผลการประเมินของคณะกรรมการประเมินกับผลการประเมินตนเอง พบว่าในระดับกองมีความสอดคล้องกันคิดเป็นร้อยละ 94.28 ส่วนในระดับภาควิชา มีความสอดคล้องกันคิดเป็นร้อยละ 96.0 The objective of this research was to study, select, and develop indicators of internal education quality assurance of the division and departments of the Education division, The Royal Thai Army Nursing College. This study was the participatory action research which composed of two phases, the first phase was the study, selection, and development of indicators, and the second phase was the validation and try out of the developed indicators. The participants in this research were 40 administrators and faculties. Data collection methods were documentation study, focused group interviews, and questionnaire survey. The research instruments included 1) the semi-structure questionnaire for the focused group interview and 2) the questionnaire about opinions regarding the appropriateness of the developed indicators. Data was analyzed by using content analysis, and agreement scores. The results revealed that the education division should conduct the internal education quality assurance for all nine components both at the division level and departments level. The indicators and criteria should be derived from the indicators of the college level as well as the criteria of the nursing institution accreditation of the Thai Nursing Council, and the indicators of curriculum quality assurance regarding to the Thai qualification framework for higher education. There was 34 indicators for the division level, and 24 indicators for the department level. Most of the indicators were the process indicators, 58.92% for the division level, anf 62.50% for the department level. Sources of the indicators mostly derived from the indicators of the college level, 70.58% for the division level, and 75.00% for the department level. The results of quality validation by experts showed IOC above 0.70 for all nine components. The agreement score were mostly above moderate level. The try out results of using the developed indicators found that both the division level and the department level were able to write the self-assessment reports for all the developed indicators. The comparison between self-assessment scores and the internal auditor committee scores had 94.28% of agreement for the division level, and 96.0% of agreement for the department level.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />